Preparação e caracterização de fibras de carbono a partir de blendas da lignina carboximetilada e álcool polivinílico - Pompêu, Gabriela Ciribelli Santos (2023)
Lignin, despite the complexity of its structure, has considerable potential for application in new products with high added value, especially in the production of carbon fiber. The kraft process, which is prevalent in the pulp and paper industry, results in large amounts of lignin as industrial waste worldwide. Several methodologies for the application of lignin mixtures with thermoplastic polymers have been studied, especially when chemical modifications are applied to improve their compatibility in a polymeric matrix. In this context, the lignin resulting from the kraft process was chemically modified through the carboxymethylation reaction (generating sodium carboxymethyl lignin - CML-Na) to be used in the formation of blends, with polyvinyl alcohol (PVAl), at concentrations of 5, 10, 15, 20% of CML-Na (v/v), which in mass percentage (g/g) corresponds respectively to 45.5, 62.5, 71.4 and 76.9%. Thus, the maximum amount of carboxymethylated lignin was determined to produce polymeric blends with PVAl and CML-Na since electrospinning with solutions of 25% concentration (v/v) was not effective. The prepared blends were electrospun under controlled conditions of 15 kV voltage, 0.5 mL h-1 flow rate, and distance from the collector and the needle tip of 10 cm. The fibers formed were visualized with the aid of SEM, evidencing the existence of the threads, and at the concentrations of 10 and 15% more homogeneous fibers were obtained. In addition, the electrospun blends were also characterized by thermal (TGA and DSC) and structural (FTIR) analyses, validating them as quality precursor materials to produce carbon fibers. From the results obtained, the electrospun nanofibers PVAl/CML-Na 5, 10, and 15% were selected for their physicochemical properties (better thermal stability, homogeneous morphology, and spinning), and submitted to the processes of thermostabilization (oxidizing atmosphere) and carbonization (inert atmosphere), respectively. The carbonized fibers were evaluated for morphological (SEM), superficial (AFM), and structural (Raman) characteristics. After the carbonization process, an increase in the porosity on the surface of the fibers was observed, due to the rupture of some surface fibers during the carbonization process. By means of structural analyses, it was identified the occurrence of modification in the structure of the fibers during the carbonization stage confirmed the conversion of PVAl/CML-Na fibers into carbon fibers through the chemical structures representative of the carbon materials presented in the Raman spectra. The work demonstrates the potential of the use of modified lignin as a suitable precursor for the preparation of carbon fiber in the various technological applications important and necessary for the reduction of environmental impact, especially in the valorization of lignin as a sustainable raw material of renewable origin for nobler purposes.